Psychosomatic Therapy and the Pursuit of Happiness: Insights from Ibn Sina’s Philosophy of the Soul and Stoicism - Chania, Salma Anggita; Hudaeri, Mohamad; Dzawafi, Agus Ali (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
The article discusses the relationship between psychosomatic therapy and happiness based on the thoughts of Ibn Sina and the Philosophy of Stoicism. Psychosomatic disorders are physical responses due to emotional stress, which in the philosophy of Ibn Sina and Stoicism can be overcome through self-transformation and soul control. Ibn Sina also emphasized the importance of tazkiyah al-nafs (purification of the soul) and the balance of body and soul in achieving holistic health and true happiness. Meanwhile, Stoicism emphasizes self-acceptance and emotional control as the key to inner peace. This research uses a qualitative method of literature with an analytical and deductive descriptive approach. Data obtained from primary and secondary texts, then analyzed thematically and comparatively. The results showed that the integration of Ibn Sina's thoughts and Stoicism in psychosomatic therapy was able to create a holistic approach to mental health, focusing on self-transformation, emotional control and balance of body and soul as a path to happiness.